Rancang bangun aplikasi berbasis web sebagai up PMPTSP terhadap sistem pelayanan izin mendirikan bangunan - Muhamad Edi Susanto; Sharyanto Sharyanto; Iskandar Zulkarnain (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
The building permit in Tanjung Duren Selatan is carried out by UP PMPTSP, the implementing unit that operates in the licensing sector. However, the process takes a lot of time, especially in checking files and consulting the applicant by the officer. This is caused by untidy files due to the absence of a computerized system. Of course, this takes a long time so that it makes the process of making the IMB a long one by the officers. This study aims to design an Information System for IMB submissions at UP PMPTSP using interviews, library studies, and observation, while the modeling uses Unifield Modeling Language (UML) using PHP as the programming language, while MySQL as the database. This information system is expected to be a solution in order to make it easier for the public and officers in inputting and making IMBs, so that the issuance of IMB SK in UP PMPTSP Kelurahan Tanjung Duren Selatan.